Research on Optical Path Trajectory Equation Based on Three Optical Wedges - Jian Jiang; Suben Lin; Junmin Zhang; Xiaogang Li; Kunpeng Zhang; Jian Guo; Fengping Li (IEEE Photonics Journal, 2024)
Rotary drilling has been recognized for its excellent drilling performance in laser drilling. However, there are few studies on the optical path trajectory equations guiding the implementation of laser rotary drilling, which has limited the development of rotary drilling. Here, the paper deduces the optical path trajectory equations by combining spatial vectors based on the three optical wedges laser drilling platform. Then, the influence of the parameters in the equation on the microhole and drilling path is discussed by using the control variable method. The results show that the three optical wedges systems can have a good drilling ability by using the parameters obtained from the optical path trajectory equations.